Asphalt Elasticity Modulus Comparison Using Modified Laboratory LWD Against UMMATA Method - Lucky Caroles (Salehan Institute of Higher Education, 2022)
Highway consultants need pavement structure strength to examine and design. With advances in computer, sensor, and microelectronic technologies, the light weight deflectometer (LWD) can measure granular and asphalt layers. This portable, easy-to-use tool is suggested. This article was designed to improve LWD Pusjatan's accuracy and distinguish it from other testing methods. This study compares the LWD Pusjatan and UMMATA (Universal Material Testing Apparatus) methods for measuring modulus of elasticity on different materials. Boussinesq elastic theory is used to compute the modulus of most LWDs. In a semi-elastic environment, modulus is the connection between pressure and displacement in a rigid or flexible basis. The deflection value is derived from the process of vibrations caused by a load delivered from a given height onto a test item, with the wave/vibration collected by an acceleration measuring instrument, such as a geophone or accelerometer. The modulus of elasticity provided by the AUDL (Laboratory Deflection Test Equipment) method is less than that produced by the UMMATA method. According to the test results, the average value of AC Base material is 7.52% less than that of AC Base. The average value of AC BC material is just over 0.3%. These results indicate that more testing is necessary when using the AUDL methodology to detect correlations that might serve as a basis for comparison. Thus, the AUDL test method may be used as a nondestructive testing technique. This kind of non-destructive technique should be used frequently so that simulations of field circumstances are more accurate. Doi: 10.28991/CEJ-2022-08-06-012 Full Text: PDF